Development of animal models to study aggressive thyroid cancers - Shovan Dutta; Jeffrey A Knauf (European Thyroid Journal)
The development of mouse models for thyroid cancer has significantly advanced over the years, enhancing our understanding of thyroid tumorigenesis, molecular pathways and treatment responses. The earliest mouse models of thyroid cancer relied on hormone, radiation or chemical carcinogenesis to induce tumors. However, as our understanding of the genetic alterations driving thyroid cancer has expanded, more sophisticated genetic engineering techniques have been employed to create models with thyroid-specific expression of these driver mutations. While driver mutations can initiate tumorigenesis, they are often insufficient to sustain cancer progression and invasion, which significantly limits their usefulness in studying advanced thyroid cancers. Recent studies exploring the genomic landscape of advanced thyroid cancer have identified several cooperating mutations, which are secondary genetic alterations that work alongside driver mutations to promote thyroid tumor progression. Indeed, mice with a combination of oncogenic drivers and common cooperating alterations have been developed, demonstrating that these alterations function in conjunction with the oncogenic driver to promote the progression to advanced thyroid cancer. These models provide important preclinical tools to explore how cooperating alterations influence the response to therapies, particularly those targeting the oncogenic driver. This review will focus on recent publications that broaden the scope of advanced thyroid cancer models by combining thyroid-specific oncogenic driver expression with various cooperating mutations.